Solid–solid phase transition study of ε-CL-20/binder composites. Issue 2 (22nd December 2015) - Guo, Changping; Wang, Dunju; Gao, Bing; Wang, Jun; Luo, Bo; Yang, Guangcheng; Nie, Fude
Abstract : The comparison of solid–solid phase transition (ε → γ polymorph) of CL-20 and Cl-20/composites revealed by DSC curves. Abstract : The solid–solid phase transition of 2, 4, 6, 8, 10, 12-hexanitro-2, 4, 6, 8, 10, 12-hexaazaisowurtzitane (CL-20)-based composites is important for understanding the effect of additives in the application of explosives. In comparison to the phase transition in the solvent, the solid–solid phase transition process is more complex, and rarely studied. To reveal the effect of binders such as glycidyl azide polymer (GAP), isocyanate desmodur (N100), polyethylene (PE), polyethylenimine (PEI), and polyvinylpyrrolidone (PVP), which were added to the CL-20 explosive, we employed in situ X-ray diffraction with temperatures from 30 to 185 °C, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry and thermogravimetry (DSC/TG), together with field emission scanning electron microscopy (FE-SEM) and particle size distribution. The in situ XRD shows that all the five CL-20-based explosive composites had regular particle sizes similar to raw CL-20. The PE/CL-20 composite has a similar phase transition temperature ( T PT ) to raw CL-20 ( T PT = 160 °C), while, for GAP/CL-20 and N100/CL-20, the T PT appeared beyond 15 and 20 °C, respectively, compared with raw CL-20. For PVP/CL-20 and PEI/CL-20, the T PT are delayed to 185 and 180 °C, respectively. The results are in agreement with the DSC and TG curves. In addition, we also investigated the molecular interactions between CL-20 and binders by FT-IR. It shows that no, or very weak, chemical bonds were formed between Cl-20 and PE; nevertheless, some chemical interaction was found between CL-20 and other binders (GAP, N100, PVP and PEI).